INTEGRATION OF PROCUREMENT VALUE: REVIEW OF ONLINE GAMERS CHARACTER IDENTIFICATION AND INFORMATION SUPPLY BEHAVIOUR - Mohammad Annas; Humairoh, Humairoh (International Journal of Social Science, 2023)
The main intention of the study was to uncover the values that online gamers held during the process of observing, assessing and finally held the procurement process. Those values been interpreted and describing a crystal-clear pattern of behavior of the gamers. Survey was conducted to identify as well as reviewed the character of the respondents whose all player of online game. The research took place at surrounding teens neighborhood with the range of age various but most dominantly by college ages. The method of random interview and quick assessment on questionnaire were held to justify the result. It was confirmed from the final observations and data analysis that character identification, integrated value and the way player feel related to the feature of the game significantly gave impact on how they made procurement pattern and intentions. Further research was suggested to observe more on the variety of respondents occupations as the spending power on game level were various.